Silicon Photonic Four-Channel Optical Add-Drop Multiplexer Enabled by Subwavelength Grating Waveguides - Behnam Naghdi; Lawrence R. Chen (IEEE Photonics Journal)
Wavelength-division multiplexing over optical links provides an effective solution for the bandwidth challenge of off-chip and on-chip communications. We demonstrate a compact silicon photonic four-channel optical add-drop multiplexer enabled by subwavelength-grating-based contradirectional couplers. Passbands of the device show on-chip insertion losses below 1.8 dB with wide 3 dB bandwidth of ∼6.7 nm suitable for coarse wavelength-division Multiplexing in short-reach optical interconnect applications. Transmission of 10 Gb/s data stream through different channels of the multiplexer results in negligible power penalties, whereas interferometric crosstalk-induced power penalties are below 2.8 dB.